Floating aquaculture sensor station - Yong, Xin Yi (2023)
Aquaculture is the production of aquatic organisms under optimal conditions, and it faces challenges due to aquatic organisms being sensitive to changes in their environment. Water quality monitoring is essential to ensure consistent survival and reproduction of aquatic organisms. Traditional manual methods are ineffective and inefficient, leading to limited sampling frequencies and human error. To prevent dangerous situations from occurring, a systematic water quality monitoring system is required. An IoT-enabled water quality monitoring system can gather real-time data and process it through cloud computing to provide the end-user with accessible information. This study developed a floating aquaculture sensor station that can collect real-time water quality parameters data and transmit it wirelessly to a designated server. The developed prototype provides accurate and accessible information of real-time water quality parameters, leading to more efficient and sustainable practices. The prototype is able to deploy and retract the sensor effectively to prevent the sensors damage from submerging in the water for too long. The developed prototype is self-sustainable in terms of power by harvesting solar energy.